The Implementation of Problem Based Learning (PBL) with Two Stay Two Stray (TSTS) to Increase Motivation and Learning Outcomes on Environmental Change Material for Class X-5 SMA Negeri 11 Semarang for the 2022/2023 Academic Year - Ain Amalia Rahmawati; Wiwi Isnaeni; Linda Retnowati (Universitas Negeri Semarang, 2023)
This research aims to determine the increase in motivation and learning outcomes of students on environmental change material through the application of problem based learning (PBL) with two stay two stray (TSTS). This research was carried out in class X-5 of SMA Negeri 11 Semarang in the 2022/2023 academic year with 36 students. There are two cycles in this research with instruments in the form of a learning motivation observation sheet and a multiple choice test at the end of the cycle for measuring learning outcomes. The research showed that the pre-cycle percentage of students who were motivated was 22.2%, while the first cycle increased to 44.5% and the second cycle increased significantly to 100%. The percentage of completeness of learning outcomes in the pre-cycle shows that 27.8% of students have completed it with an average score of 59.2. Observations in cycle I showed an increase to 63.9% of students completing their learning outcomes with an average of 74.3 and cycle II increasing to 88.9% of students completing it with an average of 90.1. Analysis of the data above concluded that there was an increase in student motivation and learning outcomes through the application of the problem based learning (PBL) model with two stay two stray (TSTS). good